Transmuscular quadratus lumborum versus lumbar plexus block for total hip arthroplasty: A retrospective propensity score matched cohort study - Sanjib D Adhikary; Anthony J Short; Kariem El-Boghdadly; Mena J Abdelmalak; Ki Jinn Chin (Wolters Kluwer Medknow Publications, 2018)
Background and Aims: Cadaveric studies have shown that injectate from transmuscular quadratus lumborum block (QLB) can spread to the lumbar plexus. Our aim was to compare analgesic efficacy of transmuscular QLB with lumbar plexus block (LPB) for patients undergoing total hip arthroplasty (THA). Material and Methods: Thirty patients receiving transmuscular QLB were propensity score matched with 30 patients receiving LPB for age, sex, ASA score, BMI, operative time, preoperative oxycodone, and intraoperative opioid use. The primary outcome was postoperative opioid consumption during the first 24 postoperative hours. Secondary outcomes included static pain scores at 0-12, 12-24, and 24-48 h intervals, opioid consumption at 0-12, 12-24, and 24-48 h intervals and the length of hospital stay. The incidence of severe adverse events was also compared. Results: Opioid consumption (median [IQR]) in the first 24 h was similar between the transmuscular QLB and LPB patient groups-33.6 mg (22.9-48.5) versus 32.8 mg (24.8-58.3) intravenous morphine equivalents. There was no difference between groups in static pain scores or opioid consumption during any time interval up to 48 h postoperatively. Length of hospital stay (median [IQR]) was similar between the transmuscular QLB and LPB groups-55.6 h (53.7-60.3) versus 57.9 h (54.3-79.1). Conclusions: This study suggests that transmuscular QLB provides similar analgesia to LPB following THA. Prospective studies are needed to confirm this.